Implementación de un negocio ambiental sostenible a través de la recuperación de vidrio en Latacunga. - Araujo Clavón, Wuhanda Lizeth (2022)
To obtain an economic benefit while taking care of the planet is a double objective for a green business, to recycle glass is to take care of the environment, glass is made at high temperatures that cause atmospheric pollution. The increase in population and consumption of goods and services has increased the amount of solid waste glass, representing a problem in environmental pollution by accumulation. This project aims to implement a sustainable environmental business through the recovery of glass, as an alternative for economic growth in the canton of Latacunga, supported with a sustainable environmental approach that has 3 aspects: social, economic and environmental as a closed system where nothing is wasted or discarded, but reused. Therefore, bibliographic research was conducted that allowed the collection of information through books, documents, with a documentary methodology to determine the category, verification and evaluation of criteria for green business followed by the creation of a green business plan. The result was a sustainable environmental business, classified as industrial eco-products, in the waste recovery and valorization subsector; meeting 65.35% of the green business criteria in a satisfactory range. In addition, it was considered as a hybrid business by means of the archetypes of business models, complying with 3 archetypes. The canton of Latacunga has a per capita production of glass waste estimated at 14304.70 kg/day as a great source for its reinsertion. At the same time, through the financing plan it was considered that the project generates competitive economic advantage, so that it is a viable and feasible business. Subsequently, the implementation of a sustainable environmental business through the recovery of glass allowed to have a sustainable development based on the design, creation and delivery of the environmental and economic value proposition, satisfying consumer needs through practices that contribute in giving a new use to the glass that is discarded and creating job opportunities.